Technology-Based Islamic Education: Building Inclusive, Adaptive, and Future-Ready Learning Foundations - Sari, Yuni Purnama; Nugraha, Jaka; Basri, Hasan (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2024)
Islamic education in the digital era faces new challenges and opportunities related to the integration of technology. This Research aims to explore the application of technology in Islamic education to support more inclusive and adaptive learning. This study uses a qualitative approach with a journal collection research method to review literature on the application of technology in Islamic education, focusing on moral, spiritual, and social principles. The findings show that technology, including e-learning platforms, mobile applications, and social media, can expand access to education, create more personalized learning experiences, and support flexible teaching methods. Effective implementation requires clear policies, training for educators, and attention to Islamic ethical principles. This research is expected to provide guidance for the development of more effective technology-based Islamic education strategies in the digital era.